"Call the witness": Romani Holocaust related art in Austria and Marika Schmiedt's will to memory. (February 2020) - Asavei, Maria Alina
Both academic and popular culture discourses are inhabited by statements that "pathologize" the ways Roma remember the Holocaust and other traumatic events. Against these claims, this article's main aim is to explore contemporary artistic production from Austria which fosters "Roma will to memory" within an assemblage of political practices and discourses. To this end, I will explore Marika Schmiedt's body of artistic memory work from 1999 to 2015, relying on a critical visual approach. The impetus for this exploration is Slawomir Kapralski's assertion that the actual cases of active remembering and commemoration among Roma and Sinti would render the traditional approach to Roma as "people without memory and history" inaccurate. As this case study shows, there is no such a thing as "Roma indifference to recollection, " but rather, the testimony about the traumatic past is silenced or obstructed by the lack of the infrastructure, the bureaucracy of the archives, and the strategic forgetting politics.